A review on Chemical and Medicobiological Applications of Capparidaceae Family - Rajesh, P.; Selvamani, P.; Latha, S.; Saraswathy, A.; Kannan, V. Rajesh (Pharmacognosy Reviews)
Medicinal plants are the nature’s gift to human being to make disease free healthy life. It plays a vital role to preserve our health. Capparidaceae family comprises various important medicinal properties distributed in tropical and subtropical India, whose medicinal usage has been reported in the traditional systems of medicine such as Ayurvedha, Siddha and Unani. Plants belongs to the Capparidaceae family has been described as a rasayana herb and has been used extensively as an adaptogen to increase the non specific resistance of antioxidant and immunostimulant effects. The C. sepiaria, C. spinosa, C. tomentosa and C. zeylanica etc., belongs to this family is reported as used in traditional medicine. The diverse phytoconstituents and various medicobiological uses of the plants belonging to this family were reviewed here.
Keywords: Caper bush; Capparidaceae; Chemistry; Pharmacology; Review